Effect of step-edge on spectral properties and planar stability of metallic bigraphene: Пористые и низкоразмерные структуры - Eremenko, V.V.; Sirenko, V.A.; Gospodarev, I.A.; Syrkin, E.S.; Feodosyev, S.B.; Bondar, I.S.; Saxena, S.S.; Feher, A.; Minakova, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Phonon and electron spectra of metallic bigraphene are analyzed in the presence of step-edge crystal imperfection. Different geometries of step-edge are considered. The dynamic planar stability of the considered structure is proved for temperatures above the ambient. The number of phonon states is shown to grow near the K-point of the first Brillouin zone, compared to pristine graphene. It is found, that this type of defects causes substantially non-uniform distribution of electron states and the pronounced increase in the number of states with energies close to Fermi energy can be expected in electron spectrum of the graphene-based compounds. The performed calculations are in good agreement with inelastic neutron, x-ray and Raman measurements.